Holy mother with Lattes: bureaucracy and face the introduction of teaching practices that enhance the religions of African origin - Passos, Leandro; Garcia Tommaselli, Guilherme Costa [UNESP]; Pereira, Gilmar Ribeiro (Univ Estadual Sudoeste Bahia, 2016)
Cultural diversity is present in several areas of Brazilian society, especially at school, where emerge more intensely social, ethnic-racial and cultural differences. Such questions have not been treated with proper pedagogical support in the school curriculum. Based on this premise, this work sought to reflect on the african-Brazilian and African cultures contemplated by Law 10.639 / 03, but not yet implemented concretely in the Basic Education curriculum as required. The school is the appropriate forum to debate and reflect the redefinition of ethnic-racial social relations and the school curriculum. Hence require consistent treatment with respect to the african-Brazilian and African religions as a support identity recognition of black people. It is by means of these affirmative action that is intended to restore their self-esteem, self-image and promote its idealization. Therefore, in the XXI century is inadmissible accept an exclusionary school that does not respect the religious values in their full cultural and ethno-racial diversity.
Keywords: Diversity; Ethnic and racial; Education; Religiousness